2018
DOI: 10.1111/ijag.12390
|View full text |Cite
|
Sign up to set email alerts
|

Laser patterning of oriented LiNbO3 crystal particle arrays in NiO‐doped lithium niobium silicate glasses

Abstract: The patterning of LiNbO3 crystals was carried out at the surface of NiO‐doped 40Li2O‐32Nb2O5‐28SiO2 (LNS) glasses using continuous‐wave Yb:YVO4 fiber laser (wavelength: 1080 nm) to gain a deeper understanding of the crystal growth in the laser‐induced crystallization in glasses. It was suggested that in the conventional crystallization in an electric furnace, NiO acts as a nucleation agent in the LNS glass and the addition of NiO suppresses the c‐axis orientation of LiNbO3 at the glass surface. It was found fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…However, it is possible to break inversion symmetry in a microscopic scale through techniques such as thermal/electrical poling and to induce second‐order optical nonlinearity . Crystallization of glasses, that is, the formation of non‐linear optical crystals, is also another effective method for inducing SHGs . Narazaki et al examined the effect of thermal poling on the second harmonic (SH) intensity of Na 2 O‐ZnO‐TeO 2 glasses and proposed that the large electric field in the anode‐side glass surface region leads to an orientation of asymmetric tellurite structural units of TeO 4 tbp and TeO 3 tp having electric dipoles.…”
Section: Approach To Unique Properties Of Teo2‐based Glassesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible to break inversion symmetry in a microscopic scale through techniques such as thermal/electrical poling and to induce second‐order optical nonlinearity . Crystallization of glasses, that is, the formation of non‐linear optical crystals, is also another effective method for inducing SHGs . Narazaki et al examined the effect of thermal poling on the second harmonic (SH) intensity of Na 2 O‐ZnO‐TeO 2 glasses and proposed that the large electric field in the anode‐side glass surface region leads to an orientation of asymmetric tellurite structural units of TeO 4 tbp and TeO 3 tp having electric dipoles.…”
Section: Approach To Unique Properties Of Teo2‐based Glassesmentioning
confidence: 99%
“…[107][108][109] Crystallization of glasses, that is, the formation of non-linear optical crystals, is also another effective method for inducing SHGs. 43,[110][111][112] Narazaki et al 107 examined the effect of thermal poling on the second harmonic (SH) intensity of Na 2 O-ZnO-TeO 2 glasses and proposed that the large electric field in the anode-side glass surface region leads to an orientation of asymmetric tellurite structural units of TeO 4 tbp and TeO 3 tp having electric dipoles. Tamagawa et al 109 applied a thermal poling (2.0 kV (DC voltage), 210°C, 40 min) to transparent glass-ceramics of 15K 2 O-15Nb 2 O 5 -68TeO 2 -2MoO 3 and found that the SH intensity of nanocrystallized glasses is enhanced, suggesting the increase in polarization in nanocrystals.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Usually, glass‐ceramics are fabricated using heat‐treatment in an electric furnace, in which glasses are heated uniformly over the whole part of a given glass. Recently, laser‐induced crystallization has received much attention, in which single crystals and nanocrystals are patterned freely in spatially selected parts in glasses, being a completely different approach to the glass‐crystallization compared with a usual crystallization technique in an electric furnace 12,20‐26 . Among glass‐ceramics reported so far, an extremely unique and curious phenomenon has been observed in the crystallization of multiferroic (ferroelectric and ferroelastic) β'‐Gd 2 (MoO 4 ) 3 (designated here as β’‐GMO) in Gd 2 O 3 ‐MoO 3 ‐B 2 O 3 glasses (GdMoBO glasses) 27‐34 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, laser-induced crystallization has received much attention, in which single crystals and nanocrystals are patterned freely in spatially selected parts in glasses, being a completely different approach to the glass-crystallization compared with a usual crystallization technique in an electric furnace. 12,[20][21][22][23][24][25][26] Among glass-ceramics reported so far, an extremely unique and curious phenomenon has been observed in the crystallization of multiferroic (ferroelectric and ferroelastic) β'-Gd 2 (MoO 4 ) 3 (designated here as β'-GMO) in Gd 2 O 3 -MoO 3 -B 2 O 3 glasses (GdMoBO glasses). [27][28][29][30][31][32][33][34] That is, crystals formed in the crystallization break into small pieces spontaneously during the crystallization in the inside of an electric furnace, not during the cooling in air after the crystallization.…”
mentioning
confidence: 99%
“…The study of thermodiffusion processes in solid ionic electrolytes provides the fundamental basis for creating gradient structures inside glass samples through local changes in the chemical composition by femtosecond laser radiation, 1–5 continuous wave (CW) laser, 6–8 by means of thermal poling, 9–11 and thermally activated ion‐exchange 12,13 …”
Section: Introductionmentioning
confidence: 99%